The Populist Theory on Social Development and It’s Marxist Criticism in Lithuania (1917-1940) - Kriščiūnas, Edvardas (Problemos, 1984)
The principal statements of the Populists (Liaudininkai), eclectic theory on social development as well as their criticism by Lithuanian Marxists who exposed the petite bourgeois nature of the above theory, its unscientific character, are considered in the article. The fundamental principle of the Populists – the greatest happiness possible for the majority of people and its reflection in economic, social, and political aspects of the theory is discussed. A conclusion on impossibility of realization of the above principle in a class society is drawn in the article.